2017
DOI: 10.1016/j.pmrj.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in Physical Medicine and Rehabilitation: A Narrative Review

Abstract: Telehealth refers to health care interactions that leverage telecommunication devices to provide medical care outside the traditional face-to-face, in-person medical encounter. Technology advances and research have expanded use of telehealth in health care delivery. Physical medicine and rehabilitation providers may use telehealth to deliver care to populations with neurologic and musculoskeletal conditions, commonly treated in both acute care and outpatient settings. Patients with impaired mobility and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(142 citation statements)
references
References 67 publications
2
127
0
4
Order By: Relevance
“…The provision of brief (ten minutes) mindfulness exercises via the internet proved a viable and accessible delivery format for an eight-week course [20]. The use of the internet and technology is a factor likely to support people with SCI in more effectively engaging in psychological interventions, given the potential functional, travel, and support-related limitations imposed by the injury [28]. Indeed, studies involving delivery of interventions in a face-to-face format demonstrated conflicting results, which could be an artefact of the potential difficulty faced by people with SCI in attending weekly and twice-weekly sessions over a period of weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of brief (ten minutes) mindfulness exercises via the internet proved a viable and accessible delivery format for an eight-week course [20]. The use of the internet and technology is a factor likely to support people with SCI in more effectively engaging in psychological interventions, given the potential functional, travel, and support-related limitations imposed by the injury [28]. Indeed, studies involving delivery of interventions in a face-to-face format demonstrated conflicting results, which could be an artefact of the potential difficulty faced by people with SCI in attending weekly and twice-weekly sessions over a period of weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been successfully applied to disorders, such as stroke [52] and paediatric headache [23], and may be a cost-effective model for provincial paediatric concussion programmes to incorporate especially where telemedicine sites require shared access to technological infrastructure and resources and where clinically indicated diagnostic tests and inperson sub-specialist consultations can be coordinated during the same visits to these centres (see Figure 1). In addition to facilitating initial assessments and follow-up appointments, recent studies suggest that other aspects of concussion care, such as psychiatric assessment and psychotherapy, follow-up for headache management, as well as cognitive rehabilitation can also be provided through telemedicine [53], thereby presenting additional potential opportunities to reduce travel costs for patients living in rural and remote communities.…”
Section: Discussionmentioning
confidence: 99%
“…This form of health care delivery most commonly uses technology that allows for both video and auditory communication to conduct clinical care outside of the traditional in‐office or hospital setting. The use of telemedicine for physiatry includes both inpatient and outpatient health care delivery, and this may be particularly important for individuals with disability and travel limitations 1 . Visits can be synchronous (real‐time interaction between patient and provider) or asynchronous.…”
Section: Introductionmentioning
confidence: 99%